Exploring effect of different resource qualities on process efficiency in construction pile installation - Page, Dominic; Hou, Lei; Rahnamayiezekavat, Payam; Antwi-Afari, Maxwell Fordjour; Han, SangHyeok; Moon, Sungkon (Journal of Civil Engineering and Management, 2023)
This paper presents the measured effects of different resource qualities on construction performance. The paper describes a recommended method, proposed with the concept of prediction by understanding the causal effect of process resources on consequent work efficiencies. The project team measured and compared the different arrangements of resources and their effects on on-site work efficiencies. The paper includes a field study of 15 operations (40 piles) in Melbourne, on several worksites of prefabricated piles and installations. It aimed to determine the causality between the set of delivered prefabricated piles and relevant work efficiencies. This field includes its purpose of generating and providing scientific evidence in effectively implementing an offsite operation. One of the critical factors affecting the efficiency of the installation process was confirmed to be the location of the longest section in the sequence. It took 21.8 minutes longer with the middle part of the installation if the longest section was designed to be in the middle of the whole prefabricated steel pile. The findings confirmed the need for holistic communication along the supply chain. The originality of this project is to provide a case study that offers archival evidence of the proposed model in a practical situation.